Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams in future. Income-maintenance or sick pay is an easier problem. Any wage- or salary-earner who is certified sick by a doctor and unable to work should be entitled, after three waiting days, to cash benefits for himself and his family at full subsistence level. But here again several millions of our fellow-citizens of working age are not wage-earners, or the dependents of wage-earners. For instance, independent shopkeepers — about a third of a million of them — and men or women working as employers do not normally suffer any loss of income when they go sick for a few days or weeks. They should have a full medical service, but as a class, they can hardly expect to be made eligible for cash benefit like the weekly wage-earners. (c) Old Age. That the aged should suffer want when they can no longer earn wages after fifty years of toil is regarded as an intolerable condition in our democracy. For thirty-five years we in Britain have sought to prevent it by providing small Old Age Pensions of various kinds. But the basic pension to-day is only 10s. per week (20s. for a couple), and that is manifestly insufficient for people who can no longer work and have no other resources. Pre-war social surveys such as that by Mr Rowntree, at York, showed that about one-third of all State pensioners were living below a reasonable human needs standard. Since then, in 1940, the State has provided Supplementary Pensions on a mild means test, and the figures show that over one-third of all pensioners have claimed and obtained such supplements from the Assistance Board. This seems to cancel out Mr Rowntree's figure. How much poverty in old age still remains no one knows. Many thousands, not being insured persons, are disentitled to any pension at all, yet they do not apply for Public Assistance. A married couple of pension ages can to-day, in certain 21 15X/2/566/303